Etruscan and Italic Studies : Journal of the Etruscan Foundation (De Gruyter, 1994)
Etruscan Studies: Journal of the Etruscan Foundation is the leading scholarly publication on Etruscology and Italic Studies in the English language.The journal details activities in all areas of research and study related to the Etruscan and pre-Roman civilizations and publishes articles as well as reviews of meetings and publications of interest to the professional community.